VALORIZED SODA LIGNIN AND ITS POSSIBLE APPLICATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The aim was to obtain a valorized soda lignin and to study its properties for the followed treatment of hardwood sawdust as a filler for obtaining a wood-polymer composite. It was shown that the treatment of aspen sawdust microparticles by their immersion into a water solution of the valorized soda lignin, that is a water-soluble soda lignin/polyethylenimine polyelectrolyte complex, leads to hydrophobisation of the sawdust particles, which in turn positively affects the mechanical performance of the obtained wood-polymer composite.